2006
DOI: 10.1007/s00167-006-0186-7
|View full text |Cite
|
Sign up to set email alerts
|

Tunnel placement in anterior cruciate ligament (ACL) reconstruction: quality control in a teaching hospital

Abstract: Correct placement of the femoral and tibial bone tunnels is decisive for a successful anterior cruciate ligament (ACL) reconstruction. Our method of tunnel placement was evaluated as part of quality control at a teaching hospital. The emphasis was placed mainly on investigating the influence of surgical experience on tunnel placement, and the effect of tunnel position on the clinical outcome. Seventeen surgeons with different levels of experience (between 0 and >150 ACL reconstructions) performed endoscopic AC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
66
0
2

Year Published

2007
2007
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 27 publications
0
66
0
2
Order By: Relevance
“…Anatomic ACL graft positioning is considered a key factor for the proper postoperative knee function and restoration of the physiological kinematics of the knee joint in ACL reconstruction 2 . However, the optimum tunnel position for positioning the graft is debatable.…”
Section: Introductionmentioning
confidence: 99%
“…Anatomic ACL graft positioning is considered a key factor for the proper postoperative knee function and restoration of the physiological kinematics of the knee joint in ACL reconstruction 2 . However, the optimum tunnel position for positioning the graft is debatable.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that incorrect positioning of the tunnels in the coronal and sagittal planes causes complications that modify the clinical results (6,7,12,16,17,20) , as well as being the commonest cause of lack of success in ACL reconstructions (21) . Several methods are currently used for assessing the positioning of the bone tunnels during or after ACL reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…These issues can lead to additional sources of failure [13]. Exact graft placement is one of the most complicated steps during ACL surgery, and large numbers of misplaced grafts have been reported [14][15][16]. These misplacements can be attributed in part to the nature of the arthroscopic procedure: The view is restricted to a local part of the ligament attachment site, and only a two-dimensional (2D) view of the three-dimensional (3D) reality can be displayed through the endoscope.…”
Section: Introductionmentioning
confidence: 99%
“…In an anatomical reconstruction with two bundles, graft placement becomes even more relevant than in single-bundle reconstructions; grafts must be positioned accurately not only with respect to the surrounding tissues, but also relative to one another. Since the femoral positioning is most important [16] and most difficult to achieve [14], this study is focused on the femoral attachment sites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation